Development of Android-Based Learning Media in the Characteristics of Trading Company Materials - Riski Rona Annisa; Kuswanto Kuswanto (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2022)
Abstract: The development of technology in the field of education provides opportunities in the use of android as a learning medium. Android is a device containing an operating system (open source) based on Linux which is widely used as a learning medium in the classroom to make the learning process more effective and efficient. This study aims to determine how the development of android-based learning media in the characteristics of trading company materials class XII IPS SMAN 6 Jambi City as an effort to meet the demands of the paradigm and how the level of feasibility of android-based learning media characteristics of trading company materials class XII IPS SMAN 6 Jambi City according to media experts, material experts, and students. This research was conducted at SMAN 6 Jambi City in April-May 2022. The development of android media uses the 4D (Define, Design, Develop, and Disseminate method. The research data was obtained using observation questionnaires to teachers in the field of economic studies as well as students, media experts and material experts. The results showed that android-based learning media material characteristics of trading companies for class XII IPS SMAN 6 Jambi City based on the assessment of media experts, material experts, teachers, and students were declared eligible or valid by obtaining a score of 119 (